ANALISIS PERBANDINGAN MAKNA PERIBAHASA MANDARIN INDONESIA YANG MENGANDUNG KATA HEWAN - Subarja, Pandi; Veronica, Tjen; Lusi, Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
Proverbs have long been used as a means of expressing thoughts and ideas. Animal play an essential role in human life, making them a common elemnt in many proverbs. Both China and Indonesia ar rich in animal species, and this is reflected in their proverbs, which often include animal-related terms. However, due to differences in social, cultural, and traditional aspects, the two nations view animal-related proverbs differently. Thus, this study, titled "A Comparative Analysis of Animal-Related Proverbs in Mandarin and Indonesian", aims to enhance readers"™ understanding of proverbs in both languages.This qualitative research was conducted through a literature review, where 138 Mandarin Proverbs and 79 Indonesian proverbs containing animal references were collected. The finfings reveal that the majority of Mandarin animal proverbs carry a negative emotional tone, accounting for 68,04%, while Indonesian animal proverbs predominantly have a neutral tone, at 44,30%. In terms of word placement, most Mandarin proverbs place animal words in the first and second positions, with 30,92%, whereas Indonesian proverbs, 90,63% of animal words are palced in the first position. Furthermore, as Indonesian Proverbs do not have a fixed word count, it was found that 34,37% consist of four charracters.